Investment Liberalization - Why a Restrictive Cross-Border Merger Policy can be Counterproductive - Pehr-Johan Norbäck; Lars Persson (The Research Institute of Industrial Economics (IUI), 2005)
Investment liberalizing countries are often concerned that cross-border mergers & acquisitions, in contrast to greenfield investments, might have an adverse effect on domestic firms and consumers. However, given that domestic assets are sufficiently scarce, we identify a preemption effect and an asset complementarity effect, which imply that the acquisition price is substantially higher than the domestic seller's profits. Moreover, we show that for the acquisition to take place, the MNE must be sufficiently efficient when using the domestic assets, otherwise rivals will expand their business, thereby making the acquisition unprofitable. Consequently, restricting cross-border M&As may also hurt consumers.
Keywords: F23; K21; L13; O12; 330; Investment Liberalization; Mergers & Acquisitions; Development; Ownership; Internationales Investitionsrecht; Deregulierung; Übernahme; Wirkungsanalyse; Theorie